PENGARUH PEMBERIAN FRAKSI ETIL ASETAT BUAH KASTURI (Mangifera casturi Kosterm) TERHADAP TOKSISITAS AKUT, GAMBARAN MAKROSKOPIS DAN MIKROSKOPIS JANTUNG TIKUS PUTIH JANTAN - Sutomo Sutomo; Gita Meliawati; Arnida Arnida (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
The kasturi plant (Mangifera casturi Kosterm) derived from the genus Mangifera, has a compound that can be utilized in the treatment. The fraction of ethyl acetate from methanol extract of M. casturi fruit contains phenolic compounds such as flavonoids and tannins with very strong of antioxidant activity. The purpose of this study was to determine the effect of ethyl acetate fraction of M. casturi on acute toxicity, macroscopic and microscopic organ picture of male rat heart. This study used a complete randomized experimental design method in the laboratory. Research on the effect of fractionation of ethyl acetate of M. casturi fruit in 4 test groups and 1 control group on acute toxicity and histology of the heart of male white rat using qualitative laboratory examination by observing the number of mouse deaths, macroscopic picture and microscopic picture of cardiac organ after giving fraction the ethyl acetate of M. casturi and the quantitative examination of LD50. Each group consisted of 5 animals given treatment once for 14 days, after which the mouse was dissected and the heart organ was taken to be observed. LD50 obtained for 2290.867 mg / kgBB. The result of analysis using Kruskal Wallis test showed that the fraction of ethyl acetate of kasturi fruit did not differ significantly between control group and treatment (p> 0.05) at mouse heart volume. All treatment groups did not show signs or inflammatory conditions, so it can be concluded that the fraction of ethyl acetate of M. casturi did not give the effect of inflammation in mouse heart organ.